2012
DOI: 10.1097/bpo.0b013e318264484c
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Trigger Thumb With Locked Interphalangeal Joint

Abstract: Level III--retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…The clinical outcomes for trigger thumb using splint therapy in five previously published reports [14][15][16][17][18] are presented in Table 2. The types and materials of splint as well as the wear time varied among these reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical outcomes for trigger thumb using splint therapy in five previously published reports [14][15][16][17][18] are presented in Table 2. The types and materials of splint as well as the wear time varied among these reports.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment offers excellent clinical results with few complications [1,4,[9][10][11][12][13]. Splint therapy provides good clinical results; reported improvement rates range from 71 to 92% [14][15][16][17][18]. The rate of spontaneous improvement is reported to range from 24 to 76% [9,10,12,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of splinting and stretching for pediatric trigger thumb have shown positive results 18,19 . Jung et al found that 80% of patients given a passive exercise protocol of passive extension of the thumb IP joint achieved IP joint extension to at least neutral at a mean follow-up of 63 months 18 .…”
Section: Pediatric Trigger Thumbmentioning
confidence: 99%
“…Jung et al found that 80% of patients given a passive exercise protocol of passive extension of the thumb IP joint achieved IP joint extension to at least neutral at a mean follow-up of 63 months 18 . Koh et al reported that 92% of locked trigger thumbs treated with splinting resolved by a mean of 22 months 19 .…”
Section: Pediatric Trigger Thumbmentioning
confidence: 99%